The Quadruple Helix Communication Model in Yogyakarta’s Creative City Development - Prayudi Prayudi; Kartika Ayu Ardhanariswari; Ninik Probosari (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
Developing a creative city is a challenge that requires the collaboration of all creative actors. It is challenging when the development of creative cities adopts the quadruple helix model. The study was essential to introduce the quadruple helix communication model. It employed a qualitative research method to understand how each creative actor communicates and collaborates in the development process of Yogyakarta as a creative city. The result found that the proposed quadruple helix communication model was the development of the transactional communication model. This model emphasized the provision of space for both one way-way and two-way communication to emerge. The quadruple helix communication model helped the development planning of Yogyakarta as a creative city. The use of one-way or two-way communication related to the achieved goal: to inform, consult, collaborate, or empower. Further, this model identified the role of each creative actor in Yogyakarta in developing the creative city.